2015
DOI: 10.1186/s13613-015-0062-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intravenous immunoglobulin therapy on behavior deficits and functions in sepsis model

Abstract: BackgroundWe aim to demonstrate behavioral alterations in a sepsis model using intravenous (IV) immunoglobulin G (IgG) and immunoglobulins enriched with IgA and IgM (IgGAM).MethodsWe divided 48 Wistar albino rats into five groups: control group, sham-operated group (only antibiotic treatment), cecal ligation and puncture (CLP) group (CLP plus antibiotic treatment), IgG group (250 mg/kg IV IgG) and IgGAM group (250 mg/kg IV IgGAM). Intravenous immunoglobulins were given 5 min after the CLP procedure. Experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…IgGAM preparation showed a better effect on the BBB integrity than a standard IgG preparation in CLP-induced septic model rats [6]. However, both immunoglobulin preparations were equally effective in reversing behavioral deficits induced by sepsis [12]. Similarly, in the current study, there were no remarkable differences between the clinical and molecular effects of two preparations with the exception that IVIgG treatment exerted a more pronounced and prolonged suppression effect on cerebral C5a receptor expression than IVIgGAM treatment.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…IgGAM preparation showed a better effect on the BBB integrity than a standard IgG preparation in CLP-induced septic model rats [6]. However, both immunoglobulin preparations were equally effective in reversing behavioral deficits induced by sepsis [12]. Similarly, in the current study, there were no remarkable differences between the clinical and molecular effects of two preparations with the exception that IVIgG treatment exerted a more pronounced and prolonged suppression effect on cerebral C5a receptor expression than IVIgGAM treatment.…”
Section: Discussionmentioning
confidence: 45%
“…Effects of IVIg treatment on sepsis-induced polyneuropathy were previously reported in a retrospective trial [11]. We recently demonstrated that IVIg treatment protects the BBB integrity, inhibits CLP-induced sickness behavior, and improves survival in septic animals [6, 12]. …”
Section: Discussionmentioning
confidence: 96%
“…The differences in mainly anxiety-related behaviors are intriguing. First, in both LPS and CLP models, basically the same molecular targets are altered: Cytokines are more frequently reported and generally affect the hippocampus [169, 176-178, 180, 183-188]; microglial activation is reported by Gao et al (2017); blood-brain barrier permeability is mentioned by Ozcan et al (2015) as one of the first mechanisms induced by the CLP model; and a decrease of neurotrophic factors is related by Gao et al (2017). Besides this, oxidative stress [181,184,188], apoptosis [184,185,187], and HPA alterations [182,183] are related (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…On day 10, the rats presented depressive-like behavior that was prevented by both treatments. However, on day 30 and on day 60 after CLP surgery, the rodents did not present depressive-like behavior [123]. Metformin: It is a drug used to treat type-2 diabetes and it exerts anti-inflammatory and anti-oxidant effect [124,125].…”
Section: Glutamatergic Neurotransmission Inhibitor (Riluzole)mentioning
confidence: 99%